THE EFFECT OF INFOGRAPHIC LEARNING MEDIA ON STUDENT CREATIVITY AND LEARNING OUTCOMES IN THE TOPIC OF INDONESIAN ECONOMIC DEVELOPMENT IN SOCIAL STUDIES FOR GRADE VIII AT MTs SUNAN KALIJOGO MAYAN, KEDIRI REGENCY - Siti Rodiyah; Larasati Widoningtyas (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The selection of an appropriate learning medium plays an important role in determining the success of the classroom learning process. Teacher-centered learning tends to make students passive, which leads to low levels of creativity and learning outcomes. Therefore, learning innovation that actively engages students is required, one of which is the use of infographic media that presents information in a visual and attractive form. This study aims to: (1) examine the effect of infographic learning media on students' creativity in the topic of Indonesian Economic Development for Grade VIII at MTs Sunan Kalijogo Mayan, Kediri Regency; (2) examine the effect of infographic learning media on students' learning outcomes in the same topic; and (3) examine the effect of infographic learning media on both creativity and learning outcomes simultaneously. This study employed a quantitative approach with a quasi-experimental design. The research sample consisted of 68 students, namely class VIII-I as the experimental class and class VIII-J as the control class, selected through purposive sampling. Data were collected through a creativity questionnaire as well as pretest and posttest of learning outcomes. Normality and homogeneity tests were conducted as prerequisite tests prior to hypothesis testing. Hypothesis testing was carried out using the Independent Sample T-Test and MANOVA with the assistance of IBM SPSS Statistics 27. The findings indicate that: (1) there is an effect of infographic learning media on students' creativity with a Sig. (2-tailed) value of 0.001 < 0.05; (2) there is an effect of infographic learning media on students' learning outcomes with a Sig. (2-tailed) value of 0.001 < 0.05; and (3) there is an effect of infographic learning media on students' creativity and learning outcomes simultaneously with a Sig. value of 0.001 < 0.05, therefore H0 is rejected and Hₐ is accepted.